The Effect of Service Quality and Employee Performance On Customer Satisfaction - Suryani, Rini; Wijayanto, Gatot; Zulkarnain, Zulkarnain; Furwanti Alwie , Alvi (Green Publisher Indonesia, 2023)
Business competition that continues to increase requires business actors to continue to provide satisfaction to customers, the organization's efforts to provide satisfaction are carried out through the quality of service and the performance of its employees. This study aims to determine the effect of service quality and satisfaction on performance. This study uses a quantitative research method with a descriptive approach. Data collection techniques in this study used questionnaires and literature studies. The research data were then analyzed by testing reliability, validity and reliability using the SPSS program. The results of the study show that service quality and employee performance partially have a positive and significant effect on customer satisfaction